Acute and sub-acute oral toxicity of ethanol extract of Cassia fistula fruit in male rats - Rizwana Abid; Riaz Mahmood (Mashhad University of Medical Sciences, 2019)
Objective: The plantCassia fistula L. (Caesalpiniaceae) is traditionally used to treat heart diseases, abdominal pain and fever. The present study was aimed to investigate the toxic effects acute and sub-acute administration of ethanol extract of C. fistula fruit (CFE) in male Wistar rats. Materials and Methods: In acute toxicity, the effects of a single oral dose (1000, 3000 and 5000 mg/kg) of CFE have been determined. Animal behaviour and mortality were determined for up to 14 days. In sub-acute study, the effects of CFE in daily single oral administration at the doses of 250, 500 and 1000 mg/kg during 28 days were determined. The blood haematological and biochemical parameters, as well as the histopathological examination of the liver, heart and kidneys were studied. Results: In acute study, a single administration of the CFE up to a dose of 5000 mg/kg did not induce mortality. Thus, the LD50 of the CFE has been estimated higher than 5000 mg/kg. In sub-acute toxicity study, administration of CFE at the doses of 250, 500 and 1000 mg/kg to rats did not induce mortality. No significant differences were found in relative organ weight, and haematological and biochemical analyses in treated groups compared to control group. No noticeable histological changes were observed in organs of CFE-treated rats compared to controls.  Conclusion: These results have shown that oral administration of C. fistula fruit did not produce any significant toxic effect in male rats. Hence, C. fistula fruit could be regarded as a safe natural product for therapeutic use.